(3TQM GdeSYhOj Ydi BOGH GdHMKs - (3GdTQhGfj, ceGd GdOjf, eSYhO Hf MSjf, (B905(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf abO bGd GdEeGe eMeO GdSeQbfOj GdefI YdjfG ef ef Ydjg GdhGgH CaVd GdfYe GdPj gh fYeI GdYbd hPdc GdhGgH gh Gddg JYGdi hdh CQOa GdeUfa s
(3BNQgG (B:s
(3hLhGHg Cf Gdbhd HgPG GdefY dG jVQfG dCfg dG jNdh EeG Cf jchf Pdc GdJbOjQ KGHJG aj GdhGbY Ch dG aMJi dh cGf Pdc GdJbOjQ KGHJG aj faS GdCeQ jJe eG PcQfG ef GdOdjd SGdeG Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3/847s
(3cTa GdXfhf (B1/39s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs